O Beautiful Border Wall, Who’s the Biggest Demagogue of All? President Trump’s Populist Tweet-Storm Blows Away His U.S. and Global Counterparts - ROE, DARRELL L (IJRDO Journal of International affairs and Global strategy, 2020)
In his two and a half years in office (January 21, 2017 to July 21, 2019) President Trump sent 9,122 tweets. During this time he used terms that have been associated with demagogic rhetoric that both divides his audience and sets up an “us” versus “them” antagonism for his own political advantage. This study compared Trump’s Twitter rhetoric in terms of demagogic content and frequency across seven key terms to a then field of twenty-five Democratic presidential candidates for 2020, as well as to several members of Trump’s cabinet and administration. The study further compared seventeen nationally influential political figures and eleven global leaders who were active on Twitter during the same time period. Finally, the study looked at key hashtags, pet phrases, and “I” statements made by the president which may evidence his demagogic traits. The history and characterization of demagogic rhetoric is explored, and complexity-extremity theory is used to explain the effect of “us” versus “them” appeals in political communication. Ultimately, President Trump was found to use demagogic verbiage more widely and on a far more frequent basis than a vast field of his American peers and international contemporaries.